Markets as Policy: A Political-Сultural Approach to Market Institutions - Нил Флигстин (Journal of Economic Sociology, 2010)
The author claims that social institutions include markets. Using the expression of “markets as policy” he investigates sociological model of action, according to which the market players are looking for stable relations and solving the problem of competition via social means. The author analyses the strong linkage between the market and the state. Basing on these statements the author provides hypotheses of how the policy on the markets is done at different stages of their development: appearance, stability and transformation periods. It is claimed that during the market formation when the actors-firms are trying to build status hierarchy the political action reminds social movements. When markets are stable the firms that are more powerful defend their positions from the potential competitors. During the transition period these firms could act for more unstable situation on the market that arises due to social movements.